Reality and Relation in Antara News Article Related to Law Revision of Corruption Eradication Commission - Diah Mutiara Isnaeni; Amrin Saragih; Nurlela Nurlela (Yayasan Visi Intan Permata, 2021)
This study aims at analyzing the reality and relation in Antara news article related to law revision of Corruption Eradication Commission (Komisi Pemberantasan Korupsi/KPK). The The reality is realized in experiential function that consists transitivity system while relation is revealed by logical function that consists of the status and its logico-semantic relation. The source of data of this study is Antara online news article. The data of this study is the clauses which are presented in the content of the news article. This study uses descriptive qualitative method by applying documentation technique and are analyzed by interactive model. After the data analyzed, it is found that the reality in Antara News realized in five of the six processes by having no occurence of behavioral process and the verbal one becomes its dominance. For its relation, both status of clause, either parataxis or hypotaxis are realized in Antara news article which are engaged in expansion and projection as the logico semantic relation. From the ten configurations of logical function, Antara News only has eight of them. The findings lead this research to have one conclusion that that Antara News, as the news article which is funded by Government is definetely pro to the government policy since they believe that the revision is prominent to strengthen the sustainability of KPK as an independent constitution to eradict coruption in Indonesia.